A Survey on Balancing Data Loss Prevention (DLP) with User Privacy in a Data-Driven World - Nurhafizah, Ahmad Zaini; Mohamad Fadli, Zolkipli (INTI International University, 2024)
Nowadays, data breaches are a major concern for industries and governments, Data Loss Prevention (DLP) solutions have become essential tools to protect sensitive information and uphold data integrity. This study examines the ever-changing field of DLP methods, highlighting the importance of maintaining a balance between protecting data and respecting user privacy in the midst of widespread data circulation. The study discusses the difficult obstacles organizations encounter when merging DLP with privacy protection through analyzing real-life examples, research findings, laws, and technology developments. The results offer useful suggestions for matching DLP projects with privacy principles to improve organizational ability to withstand data breaches while also protecting individual privacy in a connected digital environment.